The "Little Red Riding Hood effect:" Fitspiration is just as bad as thinspiration for women's body satisfaction. (March 2021) - Dignard, Nicole A.L.; Jarry, Josée L.
Highlights: Fitspiration and thinspiration are associated with reduced body satisfaction. Effects of fitspiration and thinspiration are mediated by appearance comparison. Appearance comparison was greater after viewing fitspiration than thinspiration. Positive body image was associated with less comparison after thinspiration. Appearance comparison was not related to positive body image after fitspiration. Abstract: Fitspiration is a popular form of social media which outwardly promotes the pursuit of health and strength rather than of thinness. Content analyses, however, suggest that it is thematically similar to thinspiration, which is primarily associated with thinness and presents disordered eating as a lifestyle choice. Exposure to both reduces body satisfaction, but their effect has not been compared. Further, positive body image may act as a protective factor by reducing engagement in appearance comparisons. Female undergraduate students ( N = 331) were randomly assigned to view fitspiration, thinspiration, or travel images, followed by measures of state body satisfaction, state appearance comparison, and positive body image. Viewing fitspiration and thinspiration resulted in lower body satisfaction than did viewing travel images. However, whereas women with higher positive body image appeared protected from thinspiration by engaging in lower appearance comparisons than did women with lower positive body image, this same effect was not observed in women who viewed fitspiration. The fact that positive body image is not protective against fitspiration suggests that fitspiration is just as harmful, if not more, than is thinspiration and highlights the need for media literacy programs targeting fitspiration and so-called "healthy living" websites.